Life after Guns : Reciprocity and Respect among Young Men in Liberia - Hardgrove, Abby V. (Abby Virginia), 1983- (Book collections on Project MUSE., 2017)
Life After Guns explores how ex-combatants and other post-war youth negotiated a depleted and difficult social and cultural landscape in the years following Liberia's fourteen-year bloody civil war. Abby Hardgrove focuses on the structural constraints and household and family organizations that either helped or limited opportunities as these young men grew into adulthood.